Robotic exoskeleton control for lower limb rehabilitation of knee joint - Ahmed, Syed Faiz; Joyo, Muhammad Kamran; Ali, Athar; Mohd Ali, Abdul Malik; Abdul Kadir, Kushsairy; Naqvi, Yarooq R.; Abu Bakar, Badri; Shah, Asadullah (Science Publishing Corporation Inc, 2018)
Wearable devices such as exoskeletons are being opted frequently during rehabilitation processes for the post stroke recovery. Such de-vices are playing important role in the development of assistive rehabilitation robotic systems. In this paper three control strategies MPC and LQR and PID are introduced which were applied to knee joint of lower limb exoskeleton model for passive exercise. The two con-trols MPC and LQR are model based control which empowers them for stable responses. In this paper the analysis of robustness of con-trol is done under the noisy and disturbance conditions. The results showed good performance of the exoskeleton model with the applied controls in the provided condition. In the future work the applied controls will be implemented on hardware.